The maturing of entrepreneurial firms: Entrepreneurial orientation, firm performance, and administrative heritage. (1st March 2016) - Cowden, Birton J.; Tang, Jintong; Bendickson, Josh
Abstract : A large body of research has exhibited the positive effect of entrepreneurial orientation (EO) on firm performance. However, research that attempts to explore what happens to high EO firms when they mature is sorely needed. Every firm establishes a heritage over time that impacts future capabilities. In the current research, we build on the international business literature to examine how a firmʼs administrative heritage moderates the long-term effects of the EO-performance relationship, examined through the firmʼs asset specificity, founder tenure, and home culture embeddedness. From this, implications are derived for EO retention and the firmʼs awareness of administrative heritage and how to shape it to their advantage.